علاقة المناخ التنظيمي في تعزيز الاستقرار الوظيفي لدى أساتذة التعليم الثانوي - العمامرة, لطفي; حوامدي, عنتر (University of Eloued جامعة الوادي, 2023)
Abstract The current study aims to find out if there is a relationship between the organizational climate and job stability at Houari Boumediene High School in Hassi Khalifa El Oued. The study applied the comprehensive survey method, as it counted all the professors of the institution, and their number was 43 male and female professors. All of them and 36 of them are valid for analysis, and these data were analyzed using the statistical package for social sciences (spss) program, and the arithmetic means, standard deviations, and correlation coefficients were relied upon, and the general question came up. Is there a relationship between the organizational climate and job stability of secondary education teachers? The results of the study concluded that there is no statistically significant correlation between organizational climate and job stability, and there is no statistically significant correlation between leadership style and job stability, and that there is a statistically significant correlation between communication style and job stability. Among the secondary education teachers at Houari Boumediene High School in Hassi Khalifa-El Oued.
دراسة ميدانية غلى أساتذة ثانوية هواري بومدين بحاسي خليفة الوادي
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: المناخ التنظيمي، le climat organisationnel, Organizational climate; الإستقرار الوظيفي، stabilité d'emploi, job stability